Thermodynamic behavior of hydrophobically modified polyacrylamide containing random distribution of hydrophobes: experimental and theoretical investigations - Hourdet, Dominique; Ducouret, Guylaine; Varghese, Sony; Badiger, Manohar V.; Wadgaonkar, Prakash P. (Polymer, 2013)
Two series of Hydrophobically Modified Polyacrylamides (HMPAMs) were prepared by free radical copolymerization of trimethylsilylacrylamide with 3-pentadecylcyclohexylacrylamide (PDCAM) or dodecylacrylamide (DDAM) followed by removal of trimethylsilyl protecting groups. The solution properties of HMPAMs were studied in dilute aqueous solution by fluorescence spectroscopy, NMR and viscometry. The properties in aqueous solution of HMPAMs clearly displayed the formation of hydrophobic interactions between alkyl stickers. While dodecyl containing HMPAMs mainly showed a progressive collapse of the copolymer coil with the increasing fraction of hydrophobic moieties (weak intra-chain associations), pentadecylcyclohexyl groups containing HMPAMs exhibited a much lower solubility in water due to strong intra- and inter-chain associations. Experimental data were analyzed using the mean field theory developed by Semenov and Rubinstein (SR) for associating polymers. Using a set of realistic parameters, taking into account the solubility of the backbone, the fraction of stickers and the strength of hydrophobic attractions, we show that the SR model offers a quantitative description of the thermodynamic properties of HMPAMs in terms of individual and collective behavior of polymers chains; i.e. swelling and phase separation, respectively. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Associating polymer; Polyacrylamide; Self-assembling